Recognition in Italy of filiation established abroad by surrogate motherhood, between transnational continuity of personal status and public policy - Marongiu Buonaiuti, Fabrizio (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
A recent judgment by the Sezioni Unite of the Italian Corte di cassazione has ruled on a highly sensible and controversial issue, concerning the compatibility with the Italian public policy of a foreign court order, establishing a bond of filiation between a child born by surrogacy and the intended father, materially the same sex spouse of the biological father, despite the absence of any genetical link. The Sezioni Unite declared that such a court order could not be recognized, as incompatible with the Italian public policy. In so deciding, they appeared to have taken a step back as compared to an earlier judgment delivered by the first civil chamber of the same Corte di cassazione in 2016, where a more favourable attitude had prevailed. As compared to the said earlier judgment, the Sezioni Unite, besides distinguishing the circumstances occurring in the two cases, provided a more flexible reading of the public policy exception in private international law, partly overruling the narrower reading provided in the earlier judgment, which had limited its scope to those principles concerning the protection of fundamental rights enshrined in international and European instruments, as well as in the Italian Constitution. In the conclusions it reaches, the judgment by the Sezioni Unite reveals a substantial alignment with the solution envisaged by the European Court of Human Rights in its Advisory Opinion of 10 April 2019, contemplating adoption by the intended, non-biological parent, as the avenue by which the right of the child to his private life with that parent might be enforced.